Producer Opinions on Antibiotic Use in the Beef Industry - T. Lee; C. D. Reinhardt; E. F. Schwandt; D. U. Thomson (Kansas Agricultural Experiment Station Research Reports, 2017)
Antibiotic use in the beef industry is of increasing interest to consumers and has become a point of discussion for producers, veterinarians, and professional scientists in recent years. With the vast amount of information available on the internet and social media, consumers are becoming more knowledgeable about beef production practices and the use of antibiotics in the food animal industries. Furthermore, scientists have devoted a large amount of time and money to research to investigate consumer opinions and perspectives about management practices used in food animal production. However, many of these investigations fail to include the opinions and perspectives of the producers who raise these animals. Therefore, the objective of this survey was to explore producer practices and opinions on antibiotic use and antibiotic resistance in the beef industry.
Keywords: antibiotics; beef cattle; antibiotic resistance